ECONOMETRIC ANALYSIS OF THE IMPROVEMENT OF CREDIT SERVICES (American Journal of Business Management, Economics and Banking, 2025)
The quality of credit services and the level of non-performing loans (NPLs) are key determinants of financial stability and banking sector soundness. This study analyzes the main factors influencing the volume of NPLs in the banking sector of Uzbekistan through advanced econometric modeling. Using monthly data from January 2020 to January 2025 obtained from the Central Bank of the Republic of Uzbekistan, we examine the impact of capital adequacy, term deposits, liquidity indicators, and other key variables on NPL dynamics. Pearson correlation analysis is applied to identify significant relationships, followed by multiple regression estimation. Diagnostic checks reveal the presence of autocorrelation and heteroskedasticity in the static model, which is addressed through dynamic modeling using ARMAX and ARIMA specifications. The ARMAX(1,1) model demonstrates that capital adequacy has a negative and statistically significant impact on NPLs, whereas term deposits and liquidity ratios exert positive effects. The final ARIMA(0,1,0) model provides a robust baseline for short-term forecasting, indicating an expected monthly increase of 300.27 units in NPL volume. The findings emphasize the importance of strengthening capital adequacy, managing liquidity prudently, and ensuring controlled deposit growth to mitigate credit risk and enhance the quality of credit services in Uzbekistan’s banking sector.